FEASIBILITY OF ULTRASOUND‐GUIDED EPIDURAL ACCESS AT THE LUMBO‐SACRAL SPACE IN DOGS. Issue 2 (3rd September 2014) - Liotta, Annalisa; Busoni, Valeria; Carrozzo, Maria Valentina; Sandersen, Charlotte; Gabriel, Annick; Bolen, Géraldine
<x xml:space="preserve">Abstract</x> Epidural injections are commonly performed blindly in veterinary medicine. The aims of this study were to describe the lumbosacral ultrasonographic anatomy and to assess the feasibility of an ultrasound‐guided epidural injection technique in dogs. A cross sectional anatomic atlas of the lumbosacral region and ex vivo ultrasound images were obtained in two cadavers to describe the ultrasound anatomy and to identify the landmarks. Sixteen normal weight canine cadavers were used to establish two variations of the technique for direct ultrasound‐guided injection, using spinal needles or epidural catheters. The technique was finally performed in two normal weight cadavers, in two overweight cadavers and in five live dogs with radiographic abnormalities resulting of the lumbosacral spine. Contrast medium was injected and CT was used to assess the success of the injection. The anatomic landmarks to carry out the procedure were the seventh lumbar vertebra, the iliac wings, and the first sacral vertebra. The target for directing the needle was the trapezoid‐shaped echogenic zone between the contiguous articular facets of the lumbosacral vertebral canal visualized in a parasagittal plane. The spinal needle or epidural catheter was inserted in a 45° craniodorsal–caudoventral direction through the subcutaneous tissue and the interarcuate ligament until reaching the epidural space. CT examination confirmed the presence of contrast medium in the epidural space in 25/25 dogs, although a variable contamination of the subarachnoid space was also noted. Findings indicated that this ultrasound‐guided epidural injection technique is feasible for normal weight and overweight dogs, with and without radiographic abnormalities of the spine.